2022-RA-1270-ESGO Quality of Life after risk-reducing surgery for breast and ovarian cancer prevention: a systematic review and meta-analysis. (20th October 2022) - Wei, Xia; Oxley, Samuel; Sideris, Michail; Kalra, Ashwin; Legood, Rosa; Manchanda, Ranjit
Abstract : Introduction/Background: RRS is the most-effective prevention for breast-cancer (BC) and ovarian-cancer (OC) in women with increased-risk. We aimed to assess the quality-of-life (QoL) impact of risk-reducing surgery (RRS) including risk-reducing-mastectomy (RRM), risk-reducing-salpingo-oophorectomy (RRSO) and risk-reducing early-salpingectomy and delayed-oophorectomy (RRESDO) through a systematic review and meta-analysis. Methodology: We searched major databases until December 2021 following a prospective protocol (PROSPERO-CRD42022319782). Qualitative-synthesis was performed to identify the impact of RRS on various QoL outcomes. Fixed-effects meta-analysis was performed to obtain pooled estimates of QoL outcomes. Results: Thirty-one studies were included (N=4151 post-RRS vs. N=3905 controls). 12/12 studies post-RRM (N=944) reported unchanged general-health QoL, and 10/16 (N=1911) post-RRSO reported unchanged/improved general-health QoL despite short-term deficits (N=578). 13/16 studies (N=1602) showed affected sexual-function post-RRSO. Meta-analysis showed a reduction (-1.21[-1.53, -0.89]; N=3070) in sexual-pleasure and an increase (1.12[0.93, 1.31]; N=1400) in sexual-discomfort using the Sexual-Activity-Questionnaire. HRT in pre-menopausal RRSO was associated (on meta-analysis) with an increase (1.16 [0.17, 2.15]; N=291) in sexual-pleasure and a decrease (-1.20 [-1.75, -0.65]; N=157) in sexual-discomfort. 4/10 studies post-RRM (N=236) showed impacted sexual-function, while 6/10 (N=572) showed stable sexual-function. 5/10 studies post-RRM (N=514) reported no body-image problems, whereas 5/10 (N=344) showed otherwise. 12/13 studies (N=1871) reported increased menopause symptoms post-RRSO with a reduction (-1.96 [-2.81, -1.10]; N=1745) in Functional-Assessment-of-Cancer-Therapy-Endocrine Subscale on meta-analysis. 5/5 studies (N=365) post-RRM and 8/10 (N=1223) post-RRSO reported unchanged/decreased cancer-related-distress. RRESDO (2 studies, N=413) resulted in better sexual-function and menopause-specific QoL. Conclusion: RRM/RRSO reduced cancer-related distress with unaffected general-health QoL. Women/clinicians should be aware of the negative impact of sexual dysfunction and menopause related symptoms from RRSO, along-with potential detrimental impact of RRM on body-image. Early salpingectomy does not appear to increase sexual dysfunction or impact menopause symptoms and RRESDO may be a promising alternative to mitigate QoL-related risks.